Modelagem de banco de dados georreferenciado para subsidiar a gestão do transporte coletivo urbano - Andrade, Elaine Matheus Messias de (2006)
Many GIS developers ignore the essential phases of the project like modeling databases, damaging the future development of the system. Considered very important to the project development, modeling will be broached in this article due to the great volume of existing data in transport systems and the need to manipulate them in a safe, reliable and fast way. In order to do it, a model for georeferenced database in being purposed, according to OMT-G graphical note model form BORGES (1997), to subsidize the management of the urban public transport. The method adopted for the modeling development was CÂMARA's (1999) abstraction levels. The application of the conceptual model developed will be carried out on a sample project considering the data referred to the public transport system raised at EMDURB Empresa Municipal de Desenvolvimento Urbano e Rural de Bauru, using a GIS SPRING tool and an Access database. Considering the difficulties the public administration finds in raising resources and the easiness to obtain these tools, considered one of public domain and another of low costs, the interested administration , specially in the medium and small cities, in introduce this model won't need great investments for the project development and the consequent procurement of georeferrenced information regarding the public transport.